2012
DOI: 10.1097/inf.0b013e31826323a4
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns of Infectious Disease Physicians for Management of Meningococcal Disease

Abstract: Infectious disease specialists vary significantly in their practices regarding several aspects of meningococcal disease diagnosis, treatment and prevention. Antimicrobial susceptibility testing for N. meningitidis is not routinely performed in many practices. Consideration of these variations would be useful when developing treatment and prevention recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Antimicrobial susceptibility testing is not widely available, but it is noteworthy that AST was performed more frequently in penicillin recipients versus nonrecipients, and a variety of AST methods were used in the clinical laboratories. Our findings are consistent with results from a recent survey of infectious disease physicians on reported practice for the management of meningococcal disease, which found that US physicians frequently continue treatment with third-generation cephalosporins rather than switching to penicillin after microbiological confirmation of N meningitidis , irrespective of the availability of AST [ 6 ]. The most common reasons for not switching included concerns about CSF penetration, a desire not to change working treatments, and the cost effectiveness and ease of use of cephalosporins.…”
Section: Discussionsupporting
confidence: 90%
“…Antimicrobial susceptibility testing is not widely available, but it is noteworthy that AST was performed more frequently in penicillin recipients versus nonrecipients, and a variety of AST methods were used in the clinical laboratories. Our findings are consistent with results from a recent survey of infectious disease physicians on reported practice for the management of meningococcal disease, which found that US physicians frequently continue treatment with third-generation cephalosporins rather than switching to penicillin after microbiological confirmation of N meningitidis , irrespective of the availability of AST [ 6 ]. The most common reasons for not switching included concerns about CSF penetration, a desire not to change working treatments, and the cost effectiveness and ease of use of cephalosporins.…”
Section: Discussionsupporting
confidence: 90%
“…There was no evidence of any clusters of penicillin G nonsusceptible cases in this study. Although penicillin G is not recommended for empirical treatment of suspected bacterial meningitis in the United States [ 2 ], it may be used as the definitive treatment when meningococcal disease is confirmed [ 3 , 28 ]. Before treatment with penicillin, susceptibility to penicillin G should be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…We will discuss here the main IDS‐related factors that could limit the impact of IDS interventions within an AMSP. First, there can be considerable variability in the antibiotic prescribing practices of IDSs, particularly if they had received training at different institutions, and especially for situations in which evidence‐based recommendations are missing or local antimicrobial guidelines do not exist . In a hospital in Singapore, IDSs and a prospective audit and feedback AMSP operated independently, with different therapy‐modifying recommendations being offered for the same inpatients in 19% (143/756) of the cases .…”
Section: Factors That Could Reduce the Impact Of Idss Within An Amspmentioning
confidence: 99%